Performance Evaluation a High gain 16dB Square 4x4 Array design Microstrip Antenna for Communication System - Mujahidin, Irfan (JAICT, 2023)
The increased gain in the antenna of the directional radiation pattern microstrip design using the 4x4 element array method was proposed in this study. The proposed antenna is designed to work in the frequency range of 11300 ”“ 11650 MHz for wearable communication systems using microwave radio transmission channels. To increase gain, the proposed antenna in optimization uses an array with 4x4 elements. From the results of the design structure, a return loss value of -35.61 dB and a VSWR of 1.1227 was obtained. The resulting bandwidth of a 4x4 element array antenna is 250. the impedance of 50.77 + h 2.88 Î© at a working frequency of 11.5GHz. The gain of the 4x4 element array antenna is 16.25 dB at a working frequency of 11500 MHz, and its maximum gain is 16.5 dB at a working frequency of 11700 MHz. Optimization with the 4x4 element array method managed to increase Gain up to 65.76% compared to the 2x2 element array design. The proposed antenna is suitable as a candidate for use in microwave radio communication systems, IoT, and Wearable antennas.